Studying protein-DNA interactions in vitro and in vivo using single-molecule photoswitching - Uphoff, S (2013)
Protein-DNA interactions govern the fundamental cellular processes of DNA replication, transcription, repair, and chromosome organisation. Despite their importance, the detailed molecular mechanisms of protein-DNA interactions and their organisation in the cell remain elusive. The complexity of molecular biology demands new experimental concepts that resolve the structural and functional diversity of biomolecules. In this thesis, I describe fluorescence methods that give a direct view on protein-DNA interactions at the single-molecule level. These methods employ photoswitching to control the number of active fluorophores in the sample. Forster Resonance Energy Transfer (FRET) measures the distance between a donor and an acceptor fluorophore to report on biomolecular structure and dynamics in vitro. Because a single distance gives only limited structural information, I developed "switchable FRET" that employs photoswitching to sequentially probe multiple FRET pairs per molecule. Switchable FRET resolved two distances within static and dynamic DNA constructs and protein-DNA complexes. Towards application of switchable FRET, I investigated aspects of the nucleotide selection mechanism of DNA polymerase. I further explored application of single-molecule imaging in the complex environment of the living cell. Photoswitching was used to resolve the precise localisations of individual fluorophores. I constructed a super-resolution fluorescence microscope to image fixed cellular structures and track the movement of individual fluorescent fusion proteins in live bacteria. I applied the method to directly visualise DNA repair processes by DNA polymerase I and ligase, generating a quantitative account of their repair rates, search times, copy numbers, and spatial distribution in the cell. I validated the approach by tracking diffusion of replisome components and their association with the replication fork. Finally, super-resolution microscopy showed dense clusters of SMC (Structural Maintenance of Chromosomes) protein complexes in vivo that have previously been hidden by the limited resolution of conventional microscopy.